Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1128/aem.03040-09
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Forest Trees on the Distribution of Mineral Weathering-Associated Bacterial Communities of the Scleroderma citrinum Mycorrhizosphere

Abstract: In acidic forest soils, availability of inorganic nutrients is a tree-growth-limiting factor. A hypothesis to explain sustainable forest development proposes that tree roots select soil microbes involved in central biogeochemical processes, such as mineral weathering, that may contribute to nutrient mobilization and tree nutrition. Here we showed, by combining soil analyses with cultivation-dependent analyses of the culturable bacterial communities associated with the widespread mycorrhizal fungus Scleroderma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
50
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 51 publications
7
50
0
Order By: Relevance
“…In addition, our cultivation-independent approach highlighted a significant enrichment of 16S rRNA gene sequences related to Burkholderia and Collimonas on obsidian and apatite. Moreover, several effective mineralweathering bacterial strains isolated in this study presented a strong homology of their 16S rRNA gene sequences with those of effective mineral-weathering bacterial strains previously isolated from the same experimental site in the rhizosphere or on mineral surfaces (33,68,69). Interestingly, significant positive correlations between the level of mineral dissolution and the relative abundance of 16S rRNA gene sequences assigned to the Betaproteobacteria class or to the Burkholderiales order were found for apatite particles incubated for 4 years in forest soil (33,34).…”
Section: Discussionmentioning
confidence: 98%
“…In addition, our cultivation-independent approach highlighted a significant enrichment of 16S rRNA gene sequences related to Burkholderia and Collimonas on obsidian and apatite. Moreover, several effective mineralweathering bacterial strains isolated in this study presented a strong homology of their 16S rRNA gene sequences with those of effective mineral-weathering bacterial strains previously isolated from the same experimental site in the rhizosphere or on mineral surfaces (33,68,69). Interestingly, significant positive correlations between the level of mineral dissolution and the relative abundance of 16S rRNA gene sequences assigned to the Betaproteobacteria class or to the Burkholderiales order were found for apatite particles incubated for 4 years in forest soil (33,34).…”
Section: Discussionmentioning
confidence: 98%
“…The expected presence of amorphous ferric oxide/oxyhydroxide coatings on the reddish brown particles attracts organic compounds (Violante et al 2002;Wagai et al 2009). Members of the order Burkholderiales have a variety of physiological traits and lifestyles (Vial et al 2011); they are able to use a wide array of compounds as carbon sources (e.g., Chiarini et al 2006;Morimoto et al 2008;Saito et al 2008) and are revealed to have efficient mineral weathering potentials (Calvaruso et al 2010). This metabolic versatility may help them survive on the reddish brown particles where organic compounds accumulate.…”
Section: Resultsmentioning
confidence: 99%
“…In this context, the release of key nutritive cations by mineral weathering processes is crucial. It is now established that, in addition to purely abiotic processes, soil microorganisms affect ion cycling and plant nutrition by releasing nutritive cations from minerals (5,10,20,21,52).…”
mentioning
confidence: 99%